A Systematic Review and Meta- Analysis of Green-Light Laser Vaporization for Superficial Bladder - Xu, Zhi; Gan, Guifen; Chen, Guojun; Wu, Guanlin (Urology Journal, 2020)
Purpose: The related research of green-light laser vaporization in the treatment of non-muscle invasive bladder cancer (NMIBC) is limited. This study focused on analyzing the effectiveness and safety of it from the perspective of an extensive literature review. Methods: A comprehensive search of CNKI, WanFang, VIP, PubMed, Embase, and CENTRAL databases for photoselective vaporization of bladder tumor and transurethral resection of bladder tumor treatment of non-muscle invasive bladder cancer (NMIBC). The search included studies from January 1996 to December 2019. Two reviewers independently screened literature, extracted data, assessed the risk of bias of included studies. RevMan 5.3 software was used for Meta-analysis. Results: A total of 18 RCTs involving 1648 patients met the predefined criteria. Meta-analysis data demonstrated that the PVBT group exhibited a significant advantage over the TURBT group in intraoperative obturator nerve reflex (RR = 0.09, 95% CI [0.04, 0.18], P< 0.001)and bladder perforation (RR = 0.14, 95% CI [0.07, 0.28], P< 0.001) and postoperative 1-year recurrence (RR = 0.52, 95% CI [0.40, 0.67], P< 0.001). The PVBT procedure has advantages over TURBT in the amount of surgical bleeding (MD = −17.27, 95% CI [−24.73, −9.81], P< 0.001) and the length of hospital stay (MD = −2.80, 95% CI [−3.82, −1.87], P< 0.001), bladder irrigation time (MD = −0.95, 95% CI [−1.49, −0.42], P< 0.001), and catheter indwelling time (MD = −2.60, 95% CI [−3.30, −1.90], P< 0.001). There was no difference between the two types of surgery in the incidence of postoperative urethral stricture (RR = 0.53, 95% CI [0.15, 1.83], P = 0.32) and the length of surgery (MD = −2.46, 95% CI [−5.37, 0.46], P = 0.10). Conclusion: Our systematic review and meta-analysis suggests that PVBT is better than TURBT as an alternative treatment for patients with NMIBC in safe aspect. However, whether it is equally effective in terms of oncological control remains to be elucidated, and additional high quality RCTs are needed to confirm our findings.